In silico analysis of single nucleotide polymorphism (rs34377097) of TBXA2R gene and pollen induced bronchial asthma susceptibility in West Bengal population, India - Ganai, Indranil; Saha, Ishita; Banerjee, Priyajit; Laha, Arghya; Sultana, Saheen; Sultana, Nasima; Biswas, Himani; Moitra, Saibal; Podder, Sanjoy (Frontiers in Immunology, 2023)
Prevalence of asthma is increasing steadily among general population in developing countries over past two decades. One of the causative agents of broncho-constriction in asthma is thromboxane A2 receptor (TBXA2R). However few studies of TBXA2R polymorphism were performed so far. The present study aimed to assess potential association of TBXA2R rs34377097 polymorphism causing missense substitution of Arginine to Leucine (R60L) among 482 patients diagnosed with pollen-induced asthma and 122 control participants from West Bengal, India. Also we performed in-silico analysis of mutated TBXA2R protein (R60L) using homology modeling. Clinical parameters like Forced expiratory volume in 1 second (FEV1), FEV1/Forced vital capacity (FVC) and Peak expiratory flow rate (PEFR) were assessed using spirometry. Patients’ sensitivity was measured by skin prick test (SPT) against 16 pollen allergens. Polymerase chain reaction-based Restriction fragment length polymorphism was done for genotyping. Structural model of wild type and homology model of polymorphic TBXA2R was generated using AlphaFold2 and MODELLER respectively. Electrostatic surface potential was calculated using APBS plugin in PyMol. Genotype frequencies differed significantly between the study groups (P=0.03). There was no significant deviation from Hardy-Weinberg equilibrium in control population (χ2=1.56). Asthmatic patients have significantly higher frequency of rs34377097TT genotype than control subjects (P=0.03). SPT of patients showed maximum sensitivity in A. indica (87.68%) followed by C. nusifera (83.29%) and C. pulcherima (74.94%). Significant difference existed for pollen sensitivity in adolescent and young adult (P=0.01) and between young and old adult (P=0.0003). Significant negative correlation was found between FEV1/FVC ratio and intensity of SPT reactions (P<0.0001). Significant association of FEV1, FEV1/FVC and PEFR was observed with pollen-induced asthma. Furthermore, risk allele T was found to be clinically correlated with lower FEV1/FVC ratio (P=0.015) in patients. Our data showed R60L polymorphism, which was conserved across mammals, significantly reduced positive electrostatic charge of polymorphic protein in cytoplasmic domain thus altered downstream pathway and induced asthma response. The present in-silico study is the first one to report association of TBXA2R rs34377097 polymorphism in an Indian population. It may be used as prognostic marker of clinical response to asthma in West Bengal and possible target of therapeutics in future.